3 sonates pour piano dédiées à Mme. la Comtesse de Browne, par Beethoven ... Oeuvre 10 ... No. [2] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (France; Paris; S. Richault, 2023)
Early edition of the Piano Sonata no. 6 in F major, op. 10, no. 2, published in Paris by S. Richault.